Eating habits and lifestyle in children with obesity during the COVID19 lockdown: a survey in an Italian center - Cipolla, Clelia; Curatola, Antonietta; Ferretti, Serena; Giugno, Giulia; Condemi, Chiara; Delogu, Angelica Bibiana; Birritella, Lisa; Lazzareschi, Ilaria (Acta Biomedica Atenei Parmensis, 2021)
Objectives: The main aim of this study was to evaluate BMI changes in children and adolescent with obesity or overweight, analyzing the possible risk factors that contributed to weight gain during a pandemic-associated lockdown. Material and Methods: The study was conducted at the Pediatric Endocrinology Department of a third-level University Hospital in Rome, including children and adolescents with overweight and obesity. Personal, anthropometrics data and other information about physical activity, eating habits and psychological aspects were collected. Results: We included in our study 64 participants, of which 33 (51.6%) were patients with overweight and 31 (48.4%) with obesity. We divided patients in two groups: patients with pre-versus post-lockdown Δ-BMI > 0 (31, 48.4%) and patients with Δ-BMI < 0 (33, 51.6%). Our data showed that patients whose BMI increased were more sedentary (p=0.024 for physical activity and p=0.005 for hours spent with videogames) during the pandemic. As for the eating habits more than half of the subjects (67.2%) had increased the consumption of homemade desserts, bread, pasta and pizza, and a worse diet was found in patients with BMI gain (p=0.000). Regarding the psychic condition the 80% of patients reported psychological discomfort, and patients with an increase in BMI had episodes of emotional feeding more frequently (p=0.016). Conclusions: The COVID19 pandemic has had disastrous effects not only directly, but also indirectly through the lockdown especially on some categories, such as adolescents with overweight and obesity. The results indicate that it also causes significant changes in lifestyle, physical inactivity and psychological problems among children and adolescents with obesity/overweight.